Driving global health transformation: The power of the One Health Approach - SANAD, Yasser (One Health & Risk Management, 2025)
In an increasingly interconnected world, the complexity of global health, environmental, and societal challenges continue to grow. Addressing these multifaceted issues requires integrated, multidisciplinary solutions that prioritize collaboration and innovation. The One Health & Risk Management journal stands at the forefront of this movement, promoting collaboration and innovation to tackle the most urgent issues of our time. The One Health approach emphasizes the interconnectedness of human, animal, and environmental health. The journal focuses on the One Health approach, a framework that recognizes the interconnectedness of human, animal, and environmental health. By exploring the full spectrum of risks emerging from the intersections of these domains, the journal addresses a broad range of global concerns. From emerging infectious diseases to environmental degradation and antimicrobial resistance, the One Health approach provides a comprehensive lens through which to understand, prevent, and manage global risks that affect all species and ecosystems. Established in 2019 by the Moldavian Biosafety and Biosecurity Association (MDBBA), the One Health & Risk Management journal marks a significant milestone in promoting interdisciplinary research and cooperation. It serves as a crucial platform for researchers, policymakers, and practitioners to exchange ideas, share knowledge, and drive the collective action needed to find effective solutions. Aligned with the global standards set by organizations such as the World Health Organization (WHO), the World Organization for Animal Health (WOAH), the Food and Agriculture Organization (FAO), and United Nations Environment Programme (UNEP), the journal offers invaluable insights into the interconnected nature of health and risk management. As we face increasingly complex global health challenges, the One Health approach is essential - not only for safeguarding public health but also for achieving broader goals of sustainable development and environmental protection. The One Health & Risk Management journal plays a pivotal role in advancing this integrated approach, contributing to global efforts for a healthier, more resilient world. Looking forward, this journal will continue to be a driving force in interdisciplinary research, fostering international collaboration, and supporting the development of innovative, effective, and scalable solutions to the challenges we face now and in the future.